Understanding the Contents of Indonesian Civil Law: A Book Review Perkembangan Hukum Perdata di Indonesia, Sudikno Mertokusumo, Genta Publishing Yogyakarta, 2019, 206 Pages, ISBN 978-602-0757-08-7 - Azhari, Reyhan Nabillah (Faculty of Law, Universitas Negeri Semarang, 2020)
The Book titled is Perkembangan Hukum Perdata Di Indonesia (Development Of Civil Law In Indonesia). Written by Sudikno Mertokusumo, SH., MS. Published by GENTA PUBLISHING in 2019 and this book is the First Printing. The book mainly talk about How far is the Civil Law Evolve from times to time in Indonesia.